The Use of AI Agents in Producing Authentic Herbal Biscuits: Cinnamon and Dates - Nurul Fathini Binti Mohd Rizal; Tan Vee Nee; Ts. Dr D’oria Islamiah Binti Rosli (Mellbaou Publisher, 2025)
This study aims to explore the use of authentic herbs such as cinnamon and dates in the production of cookies as alternatives to artificial flavors often associated with health issues. The study employs the New Product Development (NPD) model and a content analysis approach to evaluate the effectiveness of these herbs in terms of taste, texture, and health benefits. AI technology is also applied to support recipe optimization, data collection, and user preference analysis. The results of the study found that the use of authentic herbs enhances the quality of cookies in terms of taste, aroma, and health value. A systematic approach through the NPD model ensures that product development is conducted comprehensively, while AI accelerates innovation with more efficient results. This study contributes to the development of healthy, natural food products that align with modern market demands.